Design and Analysis for the Y-axis linking Part of PCB Drilling Machine - Feida Ma; Changtao Cai; Liangjin Cai; Jingxing Qi (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at the problem of the printed circuit board (PCB) Y axis linking part, we establish the 3D three-dimension model by using the Solidworks software , analysis the structure of the linking part and making appropriate solutions according to its works process and machining process. Finally, we use finite element method to analysis with COSMOSwork software to find the priory solution, improve the R&D speed, reduce processing costs and provide a reliable basis for the machine tool structure optimization design. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2362